The impact of electron beam irradiation on Low density polyethylene and Ethylene vinyl acetate - Sabet, M. (Institute of Physics Publishing, 2017)
Improvement of measured gel content, hardness, tensile strength and elongation at break of Ethylene vinyl acetate (EVA) have confirmed positive effect of electron beam irradiation on EVA. Results obtained from both gel content tests show that degree of cross-linking in amorphous regions is dependent on dose. A significant improvement in tensile strength of neat EVA samples is obtained upon electron-beam radiation up to 210 kGy. Similarly, hardness properties of Low-density polyethylene (LDPE) improvewith increasing electron beam irradiation. This article deals with the impacts of electron beam (EB) irradiation on the properties of LDPE and Ethylene-Vinyl Acetate (EVA) as the two common based formulations for wire and cable applications. © Published under licence by IOP Publishing Ltd.